Prehospital Tourniquets Placed on Limbs Without Major Vascular Injuries, Has the Pendulum Swung Too Far?. Issue 9 (September 2022) - Legare, Timothy; Schroll, Rebecca; Hunt, John P.; Duchesne, Juan; Marr, Alan; Schoen, Jonathan; Greiffenstein, Patrick; Stuke, Lance; Smith, Alison
Background: Combat applications of tourniquets for extremity trauma have led to increased civilian prehospital tourniquet use. Studies have demonstrated that appropriate prehospital tourniquet application can decrease the incidence of arrival in shock without increasing limb complications. The aim of this study was to examine outcomes of prehospital tourniquet placement without definitive vascular injury. Methods: Retrospective review was performed of a prospectively maintained database by the American Association for the Surgery of Trauma from 29 trauma centers. Patients in this subset analysis did not have a significant vascular injury as determined by imaging or intra-operatively. Patients who received prehospital tourniquets (PHTQ) were compared to patients without prehospital tourniquets (No-PHTQ). Outcomes were amputation rates, nerve palsy, compartment syndrome, and in-hospital mortality. Results: A total of 622 patients had no major vascular injury. The incidence of patients without major vascular injury was higher in the PHTQ group (n = 585/962, 60.8 vs n = 37/88, 42.0%, P < .001). Cohorts were similar in age, gender, penetrating mechanism, injury severity scores (ISS), abbreviated injury score (AIS), and mortality ( P > .05). Amputation rates were 8.3% (n = 49/585) in the PHTQ group compared to 0% (n = 0/37) in the No-PHTQ group. Amputation rates were higher in PHTQ than No-PHTQ with similar ISS and AIS ( P = .96, P = .59). The incidence of nerve palsy and compartment syndrome was not different ( P > .05). Conclusions: This study showed a significant amount of prehospital tourniquets are being placed on patients without vascular injuries. Further studies are needed to elucidate the appropriateness of prehospital tourniquets, including targeted education of tourniquet placement.